Bovine manure as a main input in fish raising for small-scale farmers in rainfed areas, Northeast Thailand - Sompong Sritatera; Gartner, Joseph A.; Edwards, Peter; Wee, Kok Leong; FAO - UNDP (Bangkok : Asian Institute of Technology, 1987)
Information from Ban Hin Lad, Northeast Thailand was used in planning a study of bovine manure as a main input in fish raising for small-scale farmers in rainfed areas in AIT campus as adaptive field trial. Nile tilapia (Oreochromis niloticus), Tawes (Puntius gonionotus) and Common carp (Cyprinus carpio) were raised in two 200 m2 ponds by using bovine manure, the main input. Para grass CBrachiaria mutica> was placed in a bamboo frame for decomposition. Leucaena CLeucaena leucocephala) and water spinach Cipomoea aguatica) were used as supplementary feeds. The trial was conducted over a period of 7 months. Fish production and growth, nutritive value of pond input s , water quality and economic assessment of the production of the system were determined. A study of the effects on the existing farming system if using all bovine manure for fish raising was conducted in the village by using Topical Rapid Rural Appraisal <Topical RRA>. Tilapia performed better than the other two species in terms of production and growth. The combination of these pond inputs provided certain amount of nutrient to the ponds but water fertility was still low and needed to be improved. The economic assessment showed that return over cash cost under village conditions was higher than that obtained under AIT campus conditions. The mean extrapolated yield of 56. 90 kg/200 m2 /year could supply 26. 17 percent of the animal protein needs of a typical family in the project village. Conflicts of using bovine manure between existing major crop enterprises and fish ponds were controversially stated by the interviewed farmers.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1987
Keywords: Fishes -- Thailand, Northeastern -- Feeding and feeds